Metabolic Syndrome, Hyperlipidemias, and Associated Clinical Markers Among Military Airmen - Malpica, Diego (Aerospace medicine and human performance, 2023)
Due to the increased overweight and obesity prevalence in Colombia, the aim of this study is to determine the frequency of metabolic syndrome (MetS) among Colombian Air Force military aviators, crews, remote piloted aircraft operators, and air traffic controllers and relationships with clinical markers. Operationally active Columbian Air Force military personnel examined periodically at the Colombian Air Force Aerospace Medical Directorate were chosen for a cross-sectional study performed among 2179 subjects. Medical history, anthropometrics, and laboratory results were analyzed and frequencies, correlations, and odds ratios were calculated. Overall prevalence of MetS was 21.7%; in subjects with BMI ≥25, frequency increased to 36% vs. those with BMI <25. Hypertriglyceridemia was present in 31%, impaired fasting glucose 12.5%, hypertension (≥130/85 mmHg) 14.4%, low HDL-C 35.2%, and increased waist circumference 46.2%. Those with three criteria were 14.6%, four criteria 5.8%, and five criteria 1.2%. Pilots had a significantly lower prevalence of MetS at 17.7% and an adjusted OR of 0.61 (0.49-0.76) than other crew; hyperuricemia was three times more likely (3.2-5.1) and hypercholesterolemia OR was 2.3 (1.9-2.9). Subjects with MetS had a significantly higher fat percentage, waist circumference, low-density lipoprotein, very low-density lipoprotein, non-high-density lipoprotein cholesterol, atherogenic index of plasma (AIP), uric acid, and white blood cell (leukocyte) count, and a lower estimated glomerular filtration rate. There is a linear relationship of the AIP and waist circumference, BMI, uric acid, and white blood cell count. MetS prevalence among Colombian Air Force aviators is lower than the general population, higher than other countries, and displays worse lipid profiles that increase cardiovascular and diabetes mellitus risk within the military.